Nanomaterials Versus The Microbial Compounds With Wound Healing Property - Salimi, Fatemeh; Mohammadipanah, Fatemeh (Frontiers in Nanotechnology, 2021)
Age and diabetes related slow-healing or chronic wounds may result in morbidity and mortality through persistent biofilms infections and prolonged inflammatory phase. Nano-materials [metal/metal oxide NPs (39%), lipid vehicles (21%), polymer NPs (19%), ceramic nanoparticles (NPs) (14%), and carbon nanomaterials (NMs) (7%)] can be introduced as a possible next-generation therapy because of either their intrinsic wound healing activity or via carrying bioactive compounds including, antibiotics, antioxidants, growth factor or stem cell. The nanomaterials have been shown to implicate in all four stages of wound healing including hemostasis (polymer NPs, ceramic NPs, nanoceria-6.1%), inflammation (liposome/ vesicles/ solid lipid NPs/ polymer NPs/ ceramic NPs/ silver NPs/ gold NPs/ nanoceria/ fullerenes/ carbon-based NPs-32.7%), proliferation (vesicles/ liposome/ solid lipid NPs/ gold NPs/ silver NPs/ iron oxide NPs/ceramic NPs/ copper NPs / self-assembling elastin-like NPs/ nanoceria/ micelle/ dendrimers/ polymer NPs-57.1%), remodeling (iron oxide NPs/ nanoceria-4.1%). Natural compounds from alkaloids, flavonoids, retinoids, volatile oil, terpenes, carotenoids, or polyphenolic compounds with proven antioxidant, anti-inflammatory, immunomodulatory, or antimicrobial characteristics are also well known for their potential to accelerate the wound healing process. In the current paper, we survey the potential and properties of nanomaterials and microbial compounds in improving the process of wound and scar healing. Finally, we review the potential biocompounds for incorporation to nano-material in perspective to designate more effective or multivalent wound healing natural or nano-based drugs.